2001
DOI: 10.1080/109374001300339809
|View full text |Cite
|
Sign up to set email alerts
|

Toxicology and Immunotoxicology of Mercury: A Comparative Review in Fish and Humans

Abstract: This review addresses an important area of environmental and mammalian toxicology by evaluating and comparing mercury-induced effects upon the immune responses of two evolutionarily divergent yet immunologically-related species. The mechanisms of mercury toxicology and immunotoxicology are described herein, including supporting data from the following: sources of exposure; bioavailability and biodistribution; metabolism; and laboratory and field investigations. Based upon the studies presented, the relative se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
102
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(104 citation statements)
references
References 243 publications
(280 reference statements)
1
102
0
1
Order By: Relevance
“…The mercury compounds are generally used in dry-cell batteries, fluorescent bulbs, arc lamps, mirrors, and in the extraction of gold and silver from ores, thermometers, dental amalgam fillings and vaccine preserver. [87][88][89][90][91] Thimerosal (ethylmercurithiosalicylic acid) is a mercury-containing compound and a preservative for the vaccine and biological products for more than 70 years. Thimerosal dissociates as 49.5% ethylmercury by weight and thiosalicylic acid and may possess higher cytotoxicity on renal cells.…”
Section: Mercurymentioning
confidence: 99%
“…The mercury compounds are generally used in dry-cell batteries, fluorescent bulbs, arc lamps, mirrors, and in the extraction of gold and silver from ores, thermometers, dental amalgam fillings and vaccine preserver. [87][88][89][90][91] Thimerosal (ethylmercurithiosalicylic acid) is a mercury-containing compound and a preservative for the vaccine and biological products for more than 70 years. Thimerosal dissociates as 49.5% ethylmercury by weight and thiosalicylic acid and may possess higher cytotoxicity on renal cells.…”
Section: Mercurymentioning
confidence: 99%
“…However, despite considerable study, no associations have been found between mercury exposure and autoimmune disease in humans, even in highly exposed workers (Moszczynski 1997;Sweet and Zelikoff 2001;Vimercati et al 2001). Experimental research in animal models of Hg-induced autoimmunity (HgIA) may suggest the reason for this.…”
mentioning
confidence: 99%
“…Mercury (Hg) is a pollutant that can cause developmental and behavioral abnormalities including impaired reproduction and decreased survival in vertebrates [1]. Methylmercury (MeHg) is the form of most concern because, unlike inorganic Hg (Hg [II]) which is readily excreted from the body, MeHg bioaccumulates and can reach harmful levels in fish tissues [2].…”
Section: Introductionmentioning
confidence: 99%